(التفاؤل ودوره في مادة التربية الإسلامية للمرحلة المتوسطة: (دراسة ميدانية: Optimism and its role in the Islamic education for the intermediate stage - Adel Fadhli, Sarah; Mohamed Adnan, Mohamed Azrien; Mahyoub Murshed, Amer Abdulwahab (Online Journal of Research in Islamic Studies, 2019)
The educational objectives are: The purposes or objectives, which the educational process seeks to achieve and reach, close or distant,The identification of objectives for any educational work is essential before embarking on this work and its implementation, because this determination greatly influences the adaptation and definition of the field of study, its methods, means and methods that achieve these goals. The objectives are often the engine of behavior. Therefore, it is incumbent on Islamic education students to define their goals first , so that they can identify the ways and means and methods that can achieve their goals and move them towards these goals strongly and effectively. When a person sets himself a specific goal activates whenever a step closer to him, And to avoid the fun and trivial things that are usually occupied by those who do not have the lofty goals, and do not know how to fill their spare time for the benefit of their lives The person who has no purpose, does not know the pleasure of work, does not taste the taste of enthusiasm, but lives his life lost, does not know where the side that gives his face , and does not know where the end, cannot determine the advantage of the way in another way, or the use of other means. Therefore, setting specific goals for Islamic education is necessary and necessary to practice the educational process in Islam, and ensure its success and continuity and development; to bear fruit with the least effort, the shortest time, and the best bid. The definition of the goals of Islamic education helps to identify the paths of scientific and civilization progress, and direct this progress to where it should go. All of which serve as protective guidelines for the deviation of education from its straight path.